Remote versus early corticosteroid wean outcomes in heart transplant recipients in the contemporary era. Issue 8 (13th July 2021) - Salgado, Benjamin C.; Fida, Nadia; Krisl, Jill; Berens, Pauline M.; Graviss, Edward. A.; Nguyen, Duc T.; Hussain, Imad; Kim, Ju H.; Suarez, Erik; Trachtenberg, Barry; Torre‐Amione, Guillermo; Bhimaraj, Arvind; et al.
Abstract: Purpose: The risks and benefits of remote corticosteroid weaning in heart transplant recipients more than 2 years post‐transplant are unknown. We compared outcomes in patients undergoing early and remote steroid weaning after heart transplantation. Methods: We performed a retrospective study (range 09, 1991–04, 2017). Primary outcomes included short‐term and long‐term mortality, allograft dysfunction, and burden of rejection. Secondary outcomes included impact on hemoglobin A1c, lipid panel, bone scan T‐score, and body mass index. Results: 63 patients underwent corticosteroid weaning between 2012 and 2017. Outcomes of patients weaned early ( n  = 34; median time from transplant = 1.1 years) were compared with those weaned late ( n  = 29; median time from transplant = 4.4 years). 52 (82.5%) patients were successfully weaned off corticosteroids. No statistically significant difference in outcomes was found between the early and late weaning groups ( p  = .20). There were no differences in allograft function ( p ‐value = .16), incidence of rejection ( p  = .46), or mortality ( p  = .15). Improvement in metabolic profile was seen in both groups but was not statistically significant. Conclusions: In heart transplant recipients, remote vs early weaning of corticosteroids is not associated with significant differences in graft function or the incidence of rejection after 1‐year follow‐up. Moreover, there were no significant differences in survival up to 3 years between the two groups.